SCOUR NEAR SPILL-THROUGH TYPE ABUTMENT ON CLEAR-WATER SCOUR CONDITION FOR MULTI-SECTION CHANNELS - Jaji Abdurrosyid; Achmad Karim Fatchan (Institut Teknologi Sepuluh Nopember (ITS), 2009)
Scour is a natural phenomenon caused by erosion due to water flow on the alluvial channel bed and channel wall. In fact, scour happened in the bridge abutment is total scour, that is a combination between local scour, general scour, and constriction scour. This research aims to find the depth of scour near abutment in clear-water scour condition. This research was carried out using recirculation flume. The channel model was a compound channel and using steady-uniform flow. The abutment model was Spill-Through type (ST). The depth of scour near abutment was measured in each 6 hours running at 9 point of position. The research result shows that the maximum scour depth happened at point of separation. The depth of scour is mostly affected by Reynold and Froude number of flow. In general, the scour pattern happened around abutment is the same at every running which can be seen in the scour contour pattern that has half horseshoe shape.